Continuity and Function of Patellar Tendon Host-Donor Suture in Tibial Allograft - Ayerza, Miguel A (2006)
Reconstruction of extensor mechanism after proximal tibia tumor resection is a major concern, especially in young and physically active patients. We evaluated patellar tendon host-donor reattachments in 42 consecutive proximal tibia allo- graft reconstructions after bone tumor resection to determine if patellar tendon length and integrity was maintained, and if active knee extension and adequate function was achieved. Patellar tendon length was radiographically measured in all patients by the Insall-Salvati index while magnetic resonance was available in 19 patients to evaluate imaging integrity. Eight patients were not available for functional assessment, leaving 34 patients for clinical evaluation with the Musculoskeletal Tumor Society scoring system. According to the Insall-Salvati index evaluation, the reconstructed patellar tendon remained stable with no elongation between preoperative and postoperative measurements (1.15 versus 1.13). Postoperative magnetic resonance images showed a continuous patellar host-donor tendon in all. Active knee extension was restored in all functionally evaluated patients with an average functional score of 26.6 points. Twenty-four patients had no extensor lag, while ten had an average residual extensor lag of 6.5 degrees . Our findings suggest patellar tendon reconstruction with allogeneic tissue from the proximal tibia allograft sutured to the recipient´s remnant patellar tendon can restore and stabilize active knee extension.